2018
DOI: 10.1111/imm.12892
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil infiltration to the brain is platelet‐dependent, and is reversed by blockade of platelet GPIbα

Abstract: SummaryNeutrophils are key components of the innate immune response, providing host defence against infection and being recruited to non‐microbial injury sites. Platelets act as a trigger for neutrophil extravasation to inflammatory sites but mechanisms and tissue‐specific aspects of these interactions are currently unclear. Here, we use bacterial endotoxin in mice to trigger an innate inflammatory response in different tissues and measure neutrophil invasion with or without platelet reduction. We show that pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“… 31 In fact, it induces the endothelial expression of ICAM-1, VCAM-1, and CXCL1, besides enhancing neutrophil trans-endothelial migration, all well-known mechanisms of brain damage after injury. 31 , 55 57 …”
Section: Discussionmentioning
confidence: 99%
“… 31 In fact, it induces the endothelial expression of ICAM-1, VCAM-1, and CXCL1, besides enhancing neutrophil trans-endothelial migration, all well-known mechanisms of brain damage after injury. 31 , 55 57 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we show how miR-98 and let-7g* confer such neuroprotection through slightly different mechanisms. The current research denotes that let-7g* attenuates CXCL1 (IL-8-mouse homolog), which can lower CXCR2 activity, which is critical for recruiting neutrophils ( Easton, 2013 ; Giles et al, 2018 ; Bernstein et al, 2020 ). This mechanism is likely responsible for a significant degree of let-7g*-induced neuroprotection; IL-8 is directly linked to endothelial activation and leukocyte recruitment ( Wu et al, 2015 ), and silencing its activity in endothelial cells strongly decreases inflammation-induced permeability ( Chen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“… 26 PMN infiltration to the brain was found to be platelet dependent, and was reversed by blockade of the platelet receptor glycoprotein Ibα. 27 The role of PMNs for stroke outcome has recently also been confirmed in an elegant transgenic animal model. Here, it was shown that PMN-expressed CD39 (a cell-surface adenosine triphosphatase) inhibits PMN invasion into the brain and hence leads to significantly reduced behavioral deficits in experimental stroke.…”
Section: Role Of Polymorphonuclear Neutrophils For Ischemic Reperfusimentioning
confidence: 94%